Implementation of the Discovery Learning Model in Islamic Education Learning to Improve Students' Logical Thinking Skills at SMA Negeri 7 Aceh Barat Daya - Ranami; Umi Kasom (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the implementation of the Discovery Learning model in Islamic Education learning as an effort to improve students’ logical thinking skills at SMA Negeri 7 Aceh Barat Daya. The background of this research lies in the low level of students’ logical reasoning in understanding Islamic concepts, which often rely on rote learning rather than analytical comprehension. This research employed a classroom action research (CAR) approach conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. Data were collected through observation, tests, and documentation, and analyzed using descriptive qualitative and quantitative methods. The results of the study indicate that the implementation of the Discovery Learning model significantly improved students’ logical thinking skills in Islamic Education learning. Students became more active in exploring problems, formulating hypotheses, and drawing conclusions based on logical reasoning and evidence from Islamic sources. Quantitative findings showed a consistent increase in students’ average test scores from cycle I to cycle II, while qualitative observations demonstrated higher engagement and deeper conceptual understanding. The study concludes that Discovery Learning is an effective pedagogical approach to fostering logical reasoning and independent learning in Islamic Education. These findings imply that integrating inquiry-based models such as Discovery Learning can enhance the quality of Islamic Education and support students in developing higher-order thinking skills in the 21st century learning context.